Decreasing time to chemotherapy administration in patients with hematologic malignancy on the inpatient APP service. Issue 28 (1st October 2022) - Fendler, Katlin; Espinosa, Gloria; Alberto, Judith; Morales, Dianne; Miraglia, Megan; Binder, Adam F
Abstract : 260 Background: Patients with hematologic malignancies are often electively admitted for chemotherapy. Through an informal survey, patients expressed the desire to start chemotherapy within 4 hours of arriving to the hospital. Not only is this an important process to address to improve patient satisfaction but also to decrease hospital length of stay. As a result, we developed a quality improvement initiative to improve our median time to chemotherapy administration from 6 hours 41 minutes to a median of 3 hours over a 6 month period from 03/01/22 to 09/01/22. Methods: Baseline data was collected, from 9/1/2021 to 12/31/2021, on all Hematologic Malignancy patients' electively admitted for chemotherapy at Thomas Jefferson University Hospital. Benchmarks in our steps to initiate chemotherapy include time from admission to placing initiate to treat order, time from initiate order to nurse releasing chemotherapy, time from nurse releasing to pharmacy review of chemotherapy order, and time from pharmacy review to administration of chemotherapy. Data was collected and analyzed. Potential interventions were discussed and prioritized. At the time of this abstract, 2 full PDSA cycles have been completed. Results: From 9/1/2021 to 12/31/2021, admissions for 40 patients with a diagnosis of a Hematologic Malignancy were evaluated. Median time from admission to administration of chemotherapy was 6 hours 41 minutes. The first intervention implemented on 03/01/22 involved a care team (i.e. chemotherapy pharmacists and nurse, bedside nurse) message via our electronic medical record communication system to notify them when the initiate to treat order was placed. PDSA 2 implemented on 05/04/22, involved releasing chemotherapy prior to confirmation of line placement. PDSA 3 is ongoing and focuses on pre-admission planning. See Table for detailed results of each PDSA. Conclusions: Increasing communication between key players in the chemotherapy process decreased time to chemotherapy administration by 2 hours. Feedback has been positive from all key players with no clear negative unintended consequences. Some of this improvement seen was due to an increased awareness of the provider to initiate treatment sooner. Ongoing interventions are currently underway with the hopes that these help achieve our goal of initiating chemotherapy in a median time of 3 hours.Steps in the Process Baseline PDSA 1 (Increase communication) PDSA 2 (Allow for chemotherapy release prior to PICC line placement) PDSA 3 (Improve Pre-Admission Planning) Dates of Assessment 9-12/2021 03/01-04/01/22 05/04/22-05/31/22 06/01/22-Ongoing N 40 20 13 Admission to Ok to initiate chemotherapy (h:mm) 2:26 1:05 0:44 Initiate to nurse release (h:mm) 1:11 0:42 1:16 Nurse release to pharmacy review (h:mm) 0:14 0:11 0:15 Pharmacy review to administration (h:mm) 2:27 2:41 3:06 Median time from admission to chemotherapy (h:mm) 6:41 4:41 5:20